The Influence of Nurses' Prehospital Education on The Anxiety of Double J Stent Removal One Day Care Patients At The Central Surgery Installation of dr. Saiful Anwar RSUD Malang - Suyatmi; Achmad Dafir Firdaus; Evi Dwi Prastiwi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Abstract The Double J Stent is a tool to prevent kidney stone fragments from blocking the patient's ureter after surgery. The procedure for removing the Double J stent tube can be done using One Day Care (ODC) or without hospitalization, but it can cause anxiety for the patient who is going to have the operation. The aim of this study was to determine the effect of prehospital education on the anxiety of Double J stent removal one-day care patients at the Central Surgery (IBS) Installation at RSUD Dr. Saiful Anwar Malang. The research was designed using a quantitative research design with a post-test-only control design approach. The sample in this study was taken using the total sampling method, so that 20 people were divided into two groups: the control group (without education) and the intervention group (with health education). The instrument used was the Zung Self-Anxiety Rating Scale (ZSAS). Results of the analysis The Mann Whitney test showed that there was a difference in the average anxiety score of Double J Stent Removal One Day Care patients at the Central Surgical Installation of Dr. Saiful Anwar Hospital, Malang, between the control and intervention groups (p value <0.05). In other words, there is an influence of prehospital educational actions on reducing anxiety in Double J Stent Removal One Day Care patients at the Central Surgical Installation of Dr. RSUD. Saiful Anwar Malang. This research is expected to become study material for hospitals to create and implement policies regarding the implementation of prehospital nurse education for Double J Stent Removal One Day Care patients at the Installation Central Surgery at Dr. Saiful Anwar Hospital, Malang. Keywords: Double J Stent, One Day Care, Anxiety Level